Photopolymerization of Imprinted Polymer with Dummy Template for the Recognition of Hydroquinone in Aqueous Medium - Norlaili binti Abu Bakar, Nurulsaidah binti Abdul Rahim, Wan Rusmawati binti Wan Mahamod, Norhayati binti Hashim, Sharifah Norain binti Mohd Sharif (Tanjung Malim, 2024)
Photopolymerization of Imprinted Polymer with Dummy Template for the Recognition of Hydroquinone in Aqueous Medium by Norlaili binti Abu Bakar, Nurulsaidah binti Abdul Rahim, Wan Rusmawati binti Wan Mahamod, Norhayati binti Hashim, Sharifah Norain binti Mohd Sharif